Understanding the Influence of Urban Form on the Physical Activity in the Open Spaces Using Photovoice Method - Shrestha, Sadichchha; Shrestha, Rehana; Shrestha, Reshma; Köckler, Heike (KEC Journal of Science and Engineering, 2023)
This study presents the photovoice approach, a participatory qualitative research tool to study the relationship between urban form and physical activity in urban open spaces. According to the World Health Organization, increased automation of daily tasks and work has decreased physical activity over recent years across all age groups. One of the significant factors that determines an active lifestyle is the way our cities are built and the urban environment is designed. This study investigates perceived beneficial or negative impact of built environment on the levels of physical activity that result for both individuals and communities.